Solanum melongena polyphenol oxidase biosensor for the electrochemical analysis of paracetamol. Issue 8 (16th November 2016) - Garcia, Luane Ferreira; Benjamin, Stephen Rathinaraj; Antunes, Rafael S.; Lopes, Flavio Marques; Somerset, Vernon Sydwill; Gil, Eric de Souza
ABSTRACT: A new strategy for the construction of a polyphenol oxidase carbon paste biosensor for paracetamol detection is reported. The eggplant ( Solanum melongena ) was processed to collect the polyphenol oxidase as an enzyme that was incorporated in the carbon paste sensor construction. The constructed sensor displayed high sensitivity and good selection for paracetamol detection and recognition. Optimized conditions included pH 6.0 (highest activity), pH 7.0 (highest stability), pulse amplitude of 50 mV, and 15% of vegetable extract per carbon paste. The sensor displayed a linear range from 20 to 200 µM, with a detection limit of 5 µM. Application of the sensor to paracetamol determination in tablet and oral solutions have shown satisfactory results. The efficiency of the method showed very good repeatability ranging between 1.26 and 1.72% relative standard deviation for interday analysis, while recoveries for paracetamol varied between 97.5 and 99.8% for the voltammetric determination. The strategy for a simple, low cost, and efficient eggplant polyphenol oxidase sensor showcased in this work provides an opportunity for the detection of other phenolic compounds in various matrices.